Pemanfaatan Media Digital Dalam Menunjang Prestasi Siswa Di SMKN 3 Bengkulu Tengah - Nurzam, Nurzam; Anggriani, Ida; Susena, Karona Cahya; Hidayah, Nenden Restu; Arsita, Bella (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this research is to conduct a thorough analysis of the utilisation of digital media in the learning process at SMKN 3 Bengkulu Tengah (High School 3 Central Bengkulu) and its impact on students' academic performance. This study adopts a qualitative approach employing a case study methodology, which involves the analysis of data gathered from interviews with teachers and students, direct observations of the learning process, and documentation of the use of digital media within the school. The findings reveal a significant enhancement in students' motivation to learn and their comprehension of concepts, as evidenced by their active participation in learning activities. However, the study also identifies several challenges encountered, such as the uneven accessibility of the internet across the school premises and the necessity for more comprehensive training for teachers to effectively leverage technology. To address these challenges, the research recommends the enhancement of teacher training, the provision of improved internet infrastructure, and the development of a curriculum that is integrated with digital technology. Through these measures, it is anticipated that the potential of digital media can be maximised to improve students' overall academic performance.